Determinants of recent immigrants' locational choices - Madeline Zavodny (Federal Reserve Bank of Atlanta, 1998)
High levels of immigration to the United States have caused the size of the foreign-born population to increase dramatically in recent years. Recent immigrants are concentrated in several states, particularly California. This paper examines the determinants of the intended state of residence of new recipients of legal permanent-resident status and new refugees over the 1989-94 period. The presence of other foreign-born people is the primary determinant of the locational choices of new legal permanent residents, but there are some differences among immigrant groups by admission category and by country of origin. Only refugees' locations appear to be sensitive to welfare generosity.
Keywords: 330; Emigration and immigration; Labor mobility